Effects of Difficult and Easy English Slogans in Advertising for Dutch Consumers. Issue 2 (3rd July 2017) - Hendriks, Berna; van Meurs, Frank; Poos, Chantal
ABSTRACT: It has been suggested that foreign languages in advertising are primarily used for their symbolic significance (the stereotypes they evoke), and that, therefore, consumers' comprehension of the foreign language used is of secondary importance. Experimental research into the effect of the difficulty of foreign languages in advertising slogans has focused on the influence of difficulty on appreciation of the slogan itself. The aim of the present study was to investigate the effect of difficult versus easy English slogans in product advertisements on evaluations extending beyond text evaluation. In a within-subjects experimental design, 128 Dutch participants evaluated six Dutch advertisements with difficult and easy English slogans. The dependent variables included evaluation of the slogan, attitudes toward the ad and product, and purchase intention. Findings showed that the easy English slogans were evaluated better than the difficult English slogans and generally resulted in a better attitude toward the ad and toward the product and in a higher purchase intention. Thus, difficult-to-understand foreign-language slogans were found to have negative effects on ad effectiveness, which extended beyond text evaluation.